Gallbladder perforation with liver abscess; laparoscopic cholecystectomy converted to open: a case report - Salas Ochoa, Edgar Salvador; Gutierrez, Maria Eugenia Dominguez; Rocha, Alfredo Lopez; Sanchez, Edilia Naraleth Arce; Moreno, Karla Itzel Altamirano; Garcia, Edna Arantxa Segura (International Journal of Research in Medical Sciences, 2021)
Gallbladder disease affects more than 20 million people in the United States. Acute cholecystitis is a clinic entity characterized by the inflammation of the vesicular wall that is usually manipulated by abdominal pain, right hypochondrial sensitivity and fever. The technique of choice for the diagnosis of cholecystitis is abdominal ultrasound; gallbladder perforation is a rare complication of acute cholecystitis (2%-11%). The presence of perivesicular abscesses is infrequent, its prevalence varies between 2.1% and 19.5%. Clinical record was reviewed of a 73 years old woman who attended a second level public care unit, with a clinical picture of acute chronic lithiasis cholecystitis, who underwent surgery consisting of open converted laparoscopic cholecystectomy with a finding of vesicular perforation with liver abscess, it was initiated with laparoscopic approach, it was not possible to identify anatomical structures, so it was decided to convert to open surgery. Cholecystectomy and abdominal lavage are usually sufficient in the treatment of gallbladder perforation.